(Invited) III-V Selective Area Growth and Epitaxial Functional Oxides on Si: From Electronic to Photonic Devices. (26th April 2016) - Merckling, Clement; Liu, Ziyang; Hsu, Mark; Hasan, Samiul; Jiang, Sijia; El Kazzi, Salim; Boccardi, Guillaume; Waldron, Niamh; Wang, Zhechao; Tian, Bin; Pantouvaki, Marianna; Van Campenhout, Joris; et al.
Abstract : This review paper presents the challenges for the monolithic integration on silicon substrate by heteroepitaxy of III-V semiconductors selective area growth as well as epitaxial functional oxides. The heteroepitaxy of these materials on a common Si platform would allow the integration of new functionalities and advanced devices in both electronic and photonic areas.